Territórios do saber x territórios do viver: formação docente em hetero-espaços no interior da Amazônia - CORDEIRO, Leonardo Zenha (Universidade Federal de Juiz de Fora, 2022)
This research illustrates the systematization of a continuous education training experience in the interior of the Brazilian Amazon, which was conducted during the post-graduation program in Education through flipped classroom pedagogy entitled: Inclusion for Emancipation in Socio-Educational Territories in Transamazon-Xingu, at the Federal University of Pará- Altamira Campus, analyzing the multiple possibilities for the final course research. The focus of this article is to explore the diversity of devices produced by different people and their socio-educational territories in the form of documentary, fanzines, workshops and cartographies in order to understand the paths to developing different types of final course research project. The data is the result of 18 months training with different people from different contexts, such as riverside, peasants, extractivists, indigenous and urban people, through multiple forms of learning made possible by different methodologies, such as the flipped classroom, blended- learning, online education and alternation pedagogy. The analyzes reveal that in the midst of multiple possibilities, the efficiency of the devices was proven to work well in these contexts.